MRI Staging of Anorectal Malignancy-A Reporting Dilemma: Is It Adenocarcinoma or Squamous Cell Carcinoma? - Anuradha Chandramohan; Kirthi Sathyakumar; Antony Augustine; Reetu John; Betty Simon; Rijo Issac; Dipti Masih; Jeba Karunya; Thomas S. Ram; Ashish Singh; Mark Ranjan Jesudason; Rohin Mittal (Thieme Medical and Scientific Publishers Pvt. Ltd., 2023)
Aim Magnetic resonance imaging (MRI) of anorectal malignancy is often reported assuming low rectal adenocarcinoma (LRC). The biopsy may, however, reveal squamous cell carcinoma (SCC). Thus, the aim was to compare the imaging findings of SCC and LRC.